Tsukamurella tyrosinosolvens - An unusual case report of bacteremic pneumonia after lung transplantation - Ménard, Armelle (BioMed Central, 2009)
BACKGROUND: Lung transplant recipients have an increased risk for actinomycetales infection secondary to immunosuppressive regimen. CASE PRESENTATION: A case of pulmonary infection with bacteremia due to Tsukamurella tyrosinosolvens in a 54-year old man who underwent a double lung transplantation four years previously is presented. CONCLUSION: The identification by conventional biochemical assays was unsuccessful and hsp gene sequencing was used to identify Tsukamurella tyrosinosolvens.